Phylogenetic analysis of the hyperthermophilic pink filament community in Octopus Spring, Yellowstone National Park. - Reysenbach, A L (1994)
The phylogenetic diversity of a well-known pink filament community associated with the 84 to 88 degrees C outflow from Octopus Spring, Yellowstone National Park, was examined. Three phylogenetic types ("phylotypes"), designated EM 3, EM 17, and EM 19, were identified by cloning and sequencing the small subunit rRNA genes (16S rDNA) obtained by PCR amplification of mixed-population DNA. All three phylotypes diverge deeply within the phylogenetic domain Bacteria sensu Woese (C. R. Woese, O. Kandler, and M. L. Wheelis, Proc. Natl. Acad. Sci. USA 87:4576-4579, 1990). No members of the Archaea or Eucarya were detected. EM 3 comprises a unique lineage within the Thermotogales group, and EM 17 and EM 19 are affiliated with the Aquificales. A total of 35 clones were examined, of which the majority (26 clones) were of a single sequence type (EM 17) closely related to Aquifex pyrophilus. In situ hybridization with clone-specific probes attributes the majority sequence, EM 17, to the pink filaments.